Cumulative fluid balance and mortality in elderly patients with acute kidney injury requiring continuous renal-replacement therapy: a multicenter prospective cohort study - Jong Hyun Jhee; Jae Yoon Park; Jung Nam An; Dong Ki Kim; Kwon Wook Joo; Yun Kyu Oh; Chun Soo Lim; Yon Su Kim; Seung Hyeok Han; Tae-Hyun Yoo; Shin-Wook Kang; Jung Pyo Lee; et al. (The Korean Society of Nephrology, 2020)
Background : The effect of fluid balance on outcomes in elderly patients with acute kidney injury (AKI) requiring continuous renal-replacement therapy (CRRT) is not explained well. We investigated outcomes according to cumulative fluid balance (CFB) in elderly patients with AKI undergoing CRRT. Methods : A total of 607 patients aged 65 years or older who started CRRT due to AKI were enrolled and stratified into two groups (fluid overload [FO] vs. no fluid overload [NFO]) based on the median CFB value for 72 hours before CRRT initiation. Propensity score-matching analysis was performed. Results : The median age of included patients was 73.0 years and 60.0% of the population was male. The median 72-hour CFB value was 2,839.0 mL. The overall cumulative survival and 28-day survival rates were lower in the FO group than in the NFO group (P < 0.001 for both) and remained so after propensity score-matching. Furthermore, patients in the FO group demonstrated a higher overall mortality risk after adjustment for age, sex, systolic blood pressure, Charlson comorbidity index, Acute Physiology and Chronic Health Evaluation II score, serum albumin, creatinine, diuretic use, and mechanical ventilation status (hazard ratio, 1.38; 95% confidence interval, 1.13 to 1.89; P < 0.001). Among survivors, both the duration of CRRT and the total duration of hospitalization from CRRT initiation showed no difference between the FO and NFO groups. Conclusion : A higher CFB value is associated with an increased risk of mortality in elderly patients with AKI requiring CRRT.